Analisa Pengujian Repeatability Timbangan Elektronik dengan Metode Syarat Teknis Timbangan Non Otomatis dan Metode NMI Australia - ponco wali (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
Testing repeat electronic scales with non-automatic scales technical requirements so far is fairly long if not using a calculator or computer. The aim of this research is to compare the repeatability testing method of electronic scales using methods according to the technical requirements of non-automatic scales and the Australian NMI method, both of which refer to OIML R76 in determining the validity or cancellation of electronic scales repeatability testing. This research method is done through repeat testing on 3 samples of electronic scales, then on each electronic scale 2 test methods are performed. The conclusion is that the electronic scales repeatability testing uses the non-automatic scales technical requirements method and the Australian NMI method has some differences although both refer to OIML R76. These differences include several points, namely the charge used, the method of adding additions, the formula for determining electronic scales, and different test results. The Australian NMI method is deemed to make it easier and more time efficient compared to the non-automatic weighing technical requirements method.